2023
DOI: 10.1021/acsbiomaterials.3c00290
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Licensed hMSCs Exhibit Enhanced Immunomodulatory Capacity in a Biomaterial Mediated Manner

Abstract: Craniomaxillofacial (CMF) bone injuries represent particularly challenging environments for regenerative healing due to their large sizes, irregular and unique defect shapes, angiogenic requirements, and mechanical stabilization needs. These defects also exhibit a heightened inflammatory environment that can complicate the healing process. This study investigates the influence of the initial inflammatory stance of human mesenchymal stem cells (hMSCs) on key osteogenic, angiogenic, and immuno­modulatory criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For example, MSCs have been shown to switch activated M1 macrophages to an M2 phenotype via prostaglandin E2. , MSC-borne chemokines, CCL2 in particular, have been found to modulate the phenotype of macrophages . Factors secreted by pro-inflammatory and anti-inflammatory macrophages activated the immunomodulatory potential of MSCs. , Inflammation-primed hMSCs exhibited higher immunomodulatory capacity compared to nonprimed cells. , All microphage phenotypes (M0,M1,M2) were demonstrated to be potent chemotactic stimulators for MSCs . Immuno-regulatory effects of placental MSCs have been found to be mediated by soluble molecules, such as IL10 and TGF-β1, acting partially via glucocorticoid receptor and progesterone receptor .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, MSCs have been shown to switch activated M1 macrophages to an M2 phenotype via prostaglandin E2. , MSC-borne chemokines, CCL2 in particular, have been found to modulate the phenotype of macrophages . Factors secreted by pro-inflammatory and anti-inflammatory macrophages activated the immunomodulatory potential of MSCs. , Inflammation-primed hMSCs exhibited higher immunomodulatory capacity compared to nonprimed cells. , All microphage phenotypes (M0,M1,M2) were demonstrated to be potent chemotactic stimulators for MSCs . Immuno-regulatory effects of placental MSCs have been found to be mediated by soluble molecules, such as IL10 and TGF-β1, acting partially via glucocorticoid receptor and progesterone receptor .…”
Section: Discussionmentioning
confidence: 99%
“… 62 Factors secreted by pro-inflammatory and anti-inflammatory macrophages activated the immunomodulatory potential of MSCs. 63 , 64 Inflammation-primed hMSCs exhibited higher immunomodulatory capacity compared to nonprimed cells. 63 , 64 All microphage phenotypes (M0,M1,M2) were demonstrated to be potent chemotactic stimulators for MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry sterile scaffolds were hydrated and crosslinked prior to cell seeding as previously described [37,56,59] and all steps were done under moderate shaking. Scaffolds were first hydrated for 2 hours in ethanol at ~20°C (room temperature).…”
Section: Mineralized Collagen Scaffold Hydrationmentioning
confidence: 99%
“…Our collaborators have shown that MSCs cultured on the mineralized collagen scaffolds promote the secretion of osteoprotegerin, which subsequently reduces osteoclast resorption in vitro [49][50][51]. Moreover, our group has used these materials to understand the antimicrobial effects of manuka honey [55], the immunomodulatory effects of placenta-derived tissues [40,44], and the crosstalk between immune cells and hMSCs [56]. Additionally, the material properties of these scaffolds are well studied and characterized in terms of stiffness (~1000 kPa dry [38,39], ~30kPa, hydrated [45]), pore size (100-200 um [39,40,42]), and pore alignment (isotropic, anisotropic [42]).…”
Section: Introductionmentioning
confidence: 99%